MEMBANGUN CITRA DESTINASI SURABAYA SEBAGAI MICE TOURISM CITY MELALUI PEMASARAN KOTA, EVENT WISATA DAN MEDIA SOSIAL - Diah Ayu Sanggarwati; Sri Lestari; Cucu Hayati (ITB AAS Indonesia Surakarta, 2025)
This research examines the strategic role of City Marketing, Event Tourism, and Social Media Marketing in shaping the destination image of Surabaya as an emerging MICE city. The main issue addressed in this research is the relatively weak influence of city marketing compared to the direct experiential factors perceived by visitors, raising questions about the effectiveness of current branding strategies in enhancing Surabaya’s competitiveness in the MICE sector. The objective of the study is to analyze the influence of these three variables on destination image and to provide strategic recommendations for strengthening Surabaya’s position as a MICE destination with cultural heritage appeal. The research employs a quantitative approach using Structural Equation Modeling (SEM) with AMOS, based on responses from 255 participants, tested through 17 indicators across 15 dimensions. The results indicate that City Marketing has a positive but less significant effect, suggesting the need for more visitor-oriented strategies, while Event Tourism and Social Media Marketing show strong positive and significant influences on destination image. These findings highlight the importance of enhancing livability, promoting unique heritage-based experiences, and leveraging digital engagement to build a stronger and more competitive destination image for Surabaya in the national and international MICE market. Keywords: Destination Image; MICE Tourism City; City Marketing; Tourism Events; Social Media